Parque Itaimbé - Santa Maria/RS: gênese de um espaço público/privado - Benaduce, Marcia Isabel de Vargas (2007)
The present study aims to investigate the process of construction of 'Itaimbé' Park, in Santa Maria, Rio Grande do Sul state to understand its current function as a public/private space. This construction was possible because of the program 'Urban Community for an Accelerated Recovery' in the administration of Osvaldo Nascimento da Silva (1977-1982). The specific objectives of this research were: to carry out an analysis of the process of usage and occupation of the park area and its surroundings in the period within the beginning of the construction and nowadays; evaluate how the transformations affected the daily lives of the inhabitants and investigate the role of the public governments in planning and executing the building. The principal methodological procedures carried out to reach these goals were: time analysis of the area through several materials, up-to-date information collecting and recognition of field space configurations, photographic survey and interviews. The result is structured in six chapters: introduction, characterization of the studied area, methodology, theoretical thesis, results and discussions and finally, conclusions and recommendations. The dissertation is still composed by the bibliography and by the attached material (texts and images which have not been included in its main body). It is concluded that the process of building the park and its consequent maintenance involved many faulty aspects: reduced popular participation, irregular alterations in the original project, wrong management, among others, it ends up not having involvement with the population and has no value as a leisure, recreational area or one which can simply be used for social co-existence. In order to change this situation it would be necessary to create new functions for that area, adapting it to the cotemporaneous demands to avoid the same historical mistakes when planning and building new parks in the city area